ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK BPHTB TERHADAP PENERIMAAN PAJAK DAERAH KOTA MANADO - Pangemanan, Hendrik Ricart; Elim, Inggriani; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2013)
Local Taxes are one source of financing local development a very reliable to support the implementation of regional autonomy. One type of regional tax levied by the City Government is Customs on Acquisition of Land and Building (BPHTB). BPHTB tax is a tax on acquisition of land and / or buildings. This study aims to determine the effectiveness and contribution of BPHTB tax to the revenue of Manado City Local Tax. The research was conducted at the Department of Revenue the city of Manado. Method of analysis used is descriptive quantitative method, namely analyzing the data of the target and realization receipts ofÂ BPHTB Tax in 2011 and 2012 by using the ratio of effectiveness and contribution ratio. The results showed that the rate of effectiveness BPHTB Tax in 2011 has not reached the target, because only reached 70.99% and in 2012 already reached the target with the percentage 116.95% which is included in the criteria is very effective. Within a period of 2 years since transitioned into Local Taxes in 2011, contributing ofÂ BPHTB tax showed a fairly good criterion contribution for Local Tax revenues in 2011 and 2012. In 2011 the percentage its contribution amounting 30.25% and in 2012 increased to 30.72%.